Recuperación de la fertilidad en una paciente estéril, mediante microcirugía de trompa uterina, y la aproximación al ovario contralateral - Aguagüiña González, Efraín (2018)
For a successful pregnancy to occur, the integrity of the female genital tract is required, highlighting as important elements the uterine tubes (TU) that transport gametes and the fertilized egg into the uterine cavity. The disease of TU due to several causes, such as ectopic pregnancy, constitute 20% of infertility causes. Thanks to the development of assisted reproduction techniques (ART) such as in vitro fertilization (IVF), in a high percentage of patients who have permanent and severe damage to these structures, surgery to repair or recanalize the uterine tubes has been displaced by This assisted reproduction technique. Tubal reanastomosis has a success rate and natural pregnancies after surgery of 9% in women with severe tubal disease at 69% in cases of mild tubal disease. We present the case of a young patient diagnosed with post-surgical infertility due to a history of two previous injured ectopic pregnancies that affected both uterine tubes and left oophorectomy; After performing the micro-surgical procedure, he recovered the possibility of being a mother.